APHRODISIAC ACTIVITY OF VENTHAMARAI MAGARANTHA CHOORANAM (STAMENS OF NELUMBONUCIFERA WHITE VARIETY) ON HEALTHY WISTER ALBINO RATS: Pharmaceutical Science-Pharmacology - S.M. VAHITHA BI; V.BANUMATHI; J. ANBU; ANJANA, ASHWINI; KUMAR, M.PITCHIAH (International Journal of Life Science and Pharma Research, 2012)
Nelumbonucifera is often used in siddha medicine as an aphrodisiac and to improve male reproductive functions.Since systematic study on these aspects are few and fare between, we studied its aphrodisiac effect on Normal wister albino rats. Adult wister albino rats were used for aphrodisiac activity protocol. Sexual behavioural parameters were observed on wister albino rats. Blood samples were collected from control and experimental rats to measure hormone testosterone. Testosterone levels showed significant increase in experimental animal compared with control. The test drug may be effective as aphrodisiac through mechanisms such as vasodilation, generation of nitric oxide, elevation of androgens and gonadotropins. It has also been documented that sexual behaviour and erection are dependent on androgen, which may act through central and peripheral mechanisms.Stamens of Nelumbonucifera white variety has definite positive effect on male sexual behaviour and increased in hormone profile.